Effect of nonmetallic solutes on the ductility of zirconium from first-principles calculations. (February 2019) - Pan, R J; Tang, A T; Wu, X Y; Wu, L; He, W; Zheng, T T
Abstract: The effect of nonmetallic solutes on the ductility of Zr-X (X = H, N, O and C) by calculating the generalized stacking-fault energies (GSFEs) of 0001 <10-10> and 11-22 <11-23> and (0001) surface energies of Zr-X binary systems using first-principles calculations. Calculation results show that all nonmetallic solutes considered here reduce both the basal and pyramidal SFEs. However, based on values of ductility parameter D, all nonmetallic alloying elements herein have not exhibited the ductility. This work provides a basis for investigating the effect of nonmetallic alloying elements on mechanical properties of zirconium alloys.